Functional principal component analyses for study of particulate matter (pm10) in the city of Bogotá (2016)
(Eng) Bogotá city air pollution is a problem that has been increasing parallel to the growth of the city. The measurements of pollution in Bogotá require methodologies that allow its analysis; therefore, at the same time, that diagnoses are issued. Below is the functional principal component analysis to reporting material particulate matter PM10. As a result, an appropriate methodology for treating large amounts of data is developed because it summarizes functional statistics such as the average and the covariance obtaining a diagnostic of the behavior of the medic results.